2010
DOI: 10.1007/s11864-010-0131-3
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture in the Oncology Setting: Clinical Trial Update

Abstract: Acupuncture, the insertion of sterile needles into acupuncture points of traditional meridians on the body, is a common and effective treatment for a number of supportive care issues in oncology including acute chemotherapy-induced nausea and vomiting. In the Integrative Oncology setting, acupuncture and Traditional Oriental Medicine have become more visible and many oncology clinics, academic health centers and comprehensive cancer centers recommend and administer acupuncture treatment. Continued basic studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Mao et al (2009) suggested that the decrease in psychological distress because of the endogenous serotonin modulation effects induced by acupuncture was a mediating factor in the resultant fatigue improvement. Similar mechanisms relating to modulation in the nervous or related systems have been suggested by authors for many other symptoms (Capodice, 2010;Sagar, 2008;Tsay, 2004).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Mao et al (2009) suggested that the decrease in psychological distress because of the endogenous serotonin modulation effects induced by acupuncture was a mediating factor in the resultant fatigue improvement. Similar mechanisms relating to modulation in the nervous or related systems have been suggested by authors for many other symptoms (Capodice, 2010;Sagar, 2008;Tsay, 2004).…”
Section: Discussionsupporting
confidence: 80%
“…Acupuncture and acupressure are potentially effective interventions for managing multiple symptoms simultaneously (Capodice, 2010;Lee & Frazier, 2011;Molassiotis et al, 2012;O'Regan & Filshie, 2010;Sagar, 2008). Studies of acupuncture or acupressure for other symptoms have revealed these concurrent effects as well (Tsay, 2004;Tsay, Cho, & Chen, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture is a CAM modality that shows promise as a component of supportive cancer care (6). In a survey study, close to half of breast cancer survivors want acupuncture to be offered in a comprehensive cancer center (5).…”
Section: Introductionmentioning
confidence: 99%
“…Acupuncture has already been established as a safe and effective evidence-based treatment for a variety of symptoms commonly experienced by oncology patients (ie, pain, fatigue, anxiety, nausea and vomiting, xerostomia, etc.) 8,9 Several small studies have reported that acupuncture may also be an effective therapeutic option in the management of lymphedema, improving clinical symptoms and reducing limb volume. [10][11][12][13] The physiology of how acupuncture may improve lymphedema is not known.…”
Section: Acupuncture and Lymphedemamentioning
confidence: 99%